The degree of impact of the admission policies of Jordanian public universities in aligning their outputs with the requirements of the labor market from the point of view of the faculty - Alofishat, Nisreen AbdAlhafed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the degree of impact of student admission policies in Jordanian universities in achieving alignment between education outcomes and labor market requirements. The study adopted the descriptive survey method, and the questionnaire was used as a tool for the study, which was distributed to a simple random sample of (300) male and female faculty members in universities. (Jordanian, Mutah, Hashemite) The results of the study showed that the degree of impact of student admission policies in Jordanian universities in achieving alignment between educational outcomes and labor market requirements has obtained a total average of (3.42 out of 5); That is, to a moderate degree, and there are statistically significant differences due to the two variables; Gender and in favor of females, and for specialization and in favor of scientific disciplines, and there are no statistically significant differences due to the academic rank variable. Based on the results, the researcher presented several recommendations and proposals for developing student admission policies in Jordanian universities and raising the level of harmonization between education outcomes and labor market requirements.
Keywords: alignment; student admission policies; education outcomes; Jordanian universities; labor market requirements